Analisis Pembentukan Wadah UKK Kelompok Tani Sawit Desa Suka Maju, Wilayah Kerja Puskesmas Tapung Hilir I, Kabupaten kampar tahun 2018.: Analysis Establishment The Work Health Efforts Of Palm Oil Farmers Group In Suka Maju Village, Tapung Hilir I Primary Health Center, Kampar District In 2018 - fatimah MKM; M.Kamali Zaman; Muhamadiah Muhamadiah (STIKes Hang Tuah Pekanbaru, 2019)
Background: Met This study uses a qualitative method of evaluation study design, with informants from elements of health centers, villages, and farmer groups. Information acquisition through interviews, brainstorming, observation and document tracking Results: The results of the research show that the public health center is severely constrained by the human resources component, while the fund resources and facilities component has been fulfilled. In the responsible elements (Village) all resources have been affected, only need cross-sector cooperation. In the implementing element (Farmers) the resources are sufficient, only need guidance for the implementation of the Work Health Efforts program. Conclusion: Suggestions for primary health care, to meet the human resource needs of primary health care, for villages to be able to utilize 7% of village funds to allocate health sector, for farmers to do horizontal communication as cadres for the establishment of Work Health Efforts. Keywords: Work Health Efforts, primary health care, Farmer Group.